First, we are going to rewrite it as a parabola equation.
Rewrite.
![8y=-x^2+2x+47](https://tex.z-dn.net/?f=8y%3D-x%5E2%2B2x%2B47)
Divide by 8.
![y=-\frac{x^2}{8}+\frac{x}{4}+\frac{47}{8}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7Bx%5E2%7D%7B8%7D%2B%5Cfrac%7Bx%7D%7B4%7D%2B%5Cfrac%7B47%7D%7B8%7D)
Factor out coefficient.
![y=-\frac{1}{8}\left(x^2-2x\right)+\frac{47}{8}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B8%7D%5Cleft%28x%5E2-2x%5Cright%29%2B%5Cfrac%7B47%7D%7B8%7D)
Then, we are going to convert x into square form.
![y=-\frac{1}{8}\left(x^2-2x+1\right)+\frac{1}{8}\cdot \:1+\frac{47}{8}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B8%7D%5Cleft%28x%5E2-2x%2B1%5Cright%29%2B%5Cfrac%7B1%7D%7B8%7D%5Ccdot%20%5C%3A1%2B%5Cfrac%7B47%7D%7B8%7D)
Convert the whole expression into square form.
![y=-\frac{1}{8}\left(x-1\right)^2+\frac{1}{8}\cdot \:1+\frac{47}{8}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B8%7D%5Cleft%28x-1%5Cright%29%5E2%2B%5Cfrac%7B1%7D%7B8%7D%5Ccdot%20%5C%3A1%2B%5Cfrac%7B47%7D%7B8%7D)
Simplify.
![y=-\frac{1}{8}\left(x-1\right)^2+6](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B1%7D%7B8%7D%5Cleft%28x-1%5Cright%29%5E2%2B6)
Subtract 6 from both sides.
![y-6=-\frac{1}{8}\left(x-1\right)^2](https://tex.z-dn.net/?f=y-6%3D-%5Cfrac%7B1%7D%7B8%7D%5Cleft%28x-1%5Cright%29%5E2)
Divide by coefficient.
![-8\left(y-6\right)=\left(x-1\right)^2](https://tex.z-dn.net/?f=-8%5Cleft%28y-6%5Cright%29%3D%5Cleft%28x-1%5Cright%29%5E2)
Rewrite in standard form.
The radius of the circle will be -2. Also, no matter what the sign says, the radius has to always be positive.
Have a nice day! :)
The equation in slope-intercept is y=0.625x+7.
y = mx + b
where:
m is the slope of the line
b is the y-intercept of the line
The slope m of the line through any two points (x1, y1) and (x2, y2) is given by:
The y-intercept b of the line is the value of y at the point where the line crosses the y axis. Since for point (x1, y1) we have y1 = mx1 + b, the y-intercept b can be calculated by:
b = y1 - mx<span>1. hope that helped</span>
Answer:
10
Step-by-step explanation:
Answer:
Step-by-step explanation:
7 feet 1 foot is 12 inches
7*12= 84 inches.
None of the choices are correct.
90 inches is 7.5 feet
62.5 inches is 5.2 feet
75 inches is 6.25 feet
45/2 can't be simplified.